1980
DOI: 10.1620/tjem.132.187
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alveolar hypercapnia on regional pulmonary perfusion.

Abstract: The effect of alveolar hypercapnia under a wide range of alveolar oxygen tensions was assessed in the right upper lobe of the normal dogs and the dogs with the reimplanted right lung. To induce alveolar hypercapnia by artificial ventilation of the right upper lobe, gas mixtures of differing oxygen fractions containing 10% or 20% CO, were used as exchange gases for the right upper lobe. The concurrent alveolar hypercapnia had little superimposed effect on the regional vascular responses to a wide range of alveo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1981
1981
2003
2003

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
(27 reference statements)
1
6
0
Order By: Relevance
“…Judging from the fact that isoproterenol can reverse the hypoxia-induced regional pulmonary vasoconstriction, stimulation of the fl-adrenergic system can modify the pulmonary vascular response to alveolar hypoxia. Once the fl-adrenergic system is blocked, stimulation of the f3-adrenergic system by isoproterenol is no longer feasible, and pulmonary vascular responses to the regional 02 tensions occur as expected from the previous reports (Isawa et al 1978b(Isawa et al , 1979(Isawa et al , 1980. Porcelli and Bergofsky (1973) reported that enhanced pulmonary pressor responses to hypoxia occurred during fl-blockade, and they attributed this enhancement to the unmasking of additional but previously antagonized a-receptors.…”
Section: Effect Of Propranolol Per Sesupporting
confidence: 53%
See 2 more Smart Citations
“…Judging from the fact that isoproterenol can reverse the hypoxia-induced regional pulmonary vasoconstriction, stimulation of the fl-adrenergic system can modify the pulmonary vascular response to alveolar hypoxia. Once the fl-adrenergic system is blocked, stimulation of the f3-adrenergic system by isoproterenol is no longer feasible, and pulmonary vascular responses to the regional 02 tensions occur as expected from the previous reports (Isawa et al 1978b(Isawa et al , 1979(Isawa et al , 1980. Porcelli and Bergofsky (1973) reported that enhanced pulmonary pressor responses to hypoxia occurred during fl-blockade, and they attributed this enhancement to the unmasking of additional but previously antagonized a-receptors.…”
Section: Effect Of Propranolol Per Sesupporting
confidence: 53%
“…Six adult mongrel dogs were studied. The experimental procedure was the same as reported previously (Isawa et al 1978a(Isawa et al , b, 1979(Isawa et al , 1980. In brief, the right upper lobe of an anesthetized normal adult mongrel dog weighing 19 to 21 kg was artificially ventilated with N2, air or approximately 60% 02 in N2, while the rest of the lungs was breathing air spontaneously.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The right upper lobe of an anesthetized dog was isolated in vivo by a balloon catheter and artificially ventilated with nitrogen (N2), air or 60% oxygen (02) in nitrogen mixed with a trace amount of helium (He), while the rest of the lungs was breathing air spontaneously as reported previously (Isawa et al 1978a(Isawa et al , b, 1979(Isawa et al , 1980(Isawa et al , 1981. Each perfusion percentage in the right upper lobe when the lobe was artificially ventilated with N2, air and 60% 02 in N2, respectively was measured by a scintillation camera (RC-IC-1205, Hitachi Medical Corporation, Tokyo) after sequentially injecting 99mTc-albumin microsphere (TCK-5, SORIN, Salingia, Italy) as a tracer material.…”
Section: Methodsmentioning
confidence: 99%
“…The purpose of the present study was to elucidate the effect of dopamine administration on the regional pulmonary perfusion in a dog lung lobe which we have used to study regional perfusion changes under various conditions (Isawa et al 1978a(Isawa et al , b, 1979(Isawa et al , 1980(Isawa et al , 1981.…”
mentioning
confidence: 99%